Isometric Exercise Intervention for Mrs. E with Uric Acid-Induced Pain Above Normal: A Case Study - Hafidh, Aditia; Puspita, Tantri (CV. Literasi Publikasi Indonesia, 2024)
Elevated uric acid levels, also known as hyperuricemia, is a metabolic condition caused by the accumulation of monosodium urate monohydrate crystals in the joints. This condition often leads to painful gout attacks, characterized by excruciating pain that is recurrent and can cause joint damage over time. The presence of uric acid crystals contributes to inflammation and pain by interacting with phospholipid membranes and serum factors. Pain management for hyperuricemia can involve both pharmacological and non-pharmacological treatments, with one such non-pharmacological approach being isometric exercise. This study aims to analyze family nursing care for a patient with elevated uric acid levels above normal and the effect of isometric exercise in reducing joint pain in Cikondang Village, Tanjung Kemuning, within the working area of UPT Puskesmas Tarogong, Garut Regency. A descriptive case study method was used, which included anamnesis, observation, physical examination, and medical record review. The case study showed that chronic pain, the primary nursing problem in this patient with elevated uric acid levels, was effectively managed through isometric exercise. This was evidenced by a reduction in the patient's pain score from moderate pain (4) to mild pain (1). The isometric exercise intervention significantly reduced joint pain in the patient with elevated uric acid levels.